Spatially and temporally targeted suppression of despotic noisy miners has conservation benefits for highly mobile and threatened woodland birds. (November 2018) - Crates, Ross; Terauds, Aleks; Rayner, Laura; Stojanovic, Dejan; Heinsohn, Robert; Wilkie, Colin; Webb, Matthew
Abstract: Interactive effects of habitat loss and interspecific competition are major threats to global biodiversity. Managing despotic competitors in modified landscapes is a conservation priority, but implementing actions to benefit rare and highly mobile species is challenging. In Australia, overabundance of hyperaggressive noisy miners following woodland fragmentation and degradation is a key threatening process given their impact on songbirds including the nomadic, critically endangered regent honeyeater. Recent studies have found rapid noisy miner recolonization following their experimental removal, questioning the efficacy of miner removal as a conservation measure. We estimated the relative habitat saturation of noisy miners at a hotspot of threatened bird diversity. We then experimentally removed 350 noisy miners and assessed the effect of this removal on subsequent noisy miner abundance, relative to a control area. We monitored the occurrence of noisy miners near regent honeyeater nests and modelled the effect of noisy miner removal on songbird populations. Noisy miner removal significantly decreased noisy miner abundance throughout the breeding season, when 15–18 regent honeyeaters nested in the miner removal area. Songbird abundance and species richness increased significantly in the miner removal area, relative to the control area. We provide a rare example of how spatially and temporally targeted preventative action can reduce threats for nomadic and highly threatened species during breeding and prevent ongoing avian diversity loss more broadly. Highlights: Experimental removal of noisy miners reduced their abundance during the breeding season. Co-occurrence of noisy miners and critically endangered regent honeyeaters during nesting decreased. Abundance and species richness of the broader songbird community increased. Preventative noisy miner suppression can be an effective conservation measure if it is targeted in space and time.